Multi‐year energy balance and carbon dioxide fluxes over a residential neighbourhood in a tropical city. (21st September 2016) - Roth, Matthias; Jansson, Christer; Velasco, Erik
ABSTRACT: Detailed eddy covariance measurements of radiation, energy and carbon dioxide fluxes over a residential neighbourhood of Singapore are presented. The measurements cover a period of ∼7 years and represent the longest set of flux data reported for a tropical city. Owing to its equatorial location, the observed radiation fluxes are uniformly high throughout the year. Annual changes in climate, energy fluxes and carbon dioxide exchange are therefore much less than observed in cities located outside the Tropics. The energy balance partitioning is nevertheless similar to that reported for subtropical and mid‐latitude suburban sites. Across the entire study period and all weather conditions 53.6% of net radiation (3.222 GJ m −2 year −1 ) is partitioned into sensible and 39.4% into latent heat, respectively, resulting in a long‐term daily Bowen ratio of ∼1.4. Significant variability exists in net radiation and sensible heat flux using a classification based on clouds and rainfall. Carbon dioxide fluxes are generally positive throughout the day with morning and evening peaks related to maxima in traffic volume separating lower day‐ from higher nighttime fluxes. Unlike in many other comparable suburban studies, net fluxes are generally higher during night‐ compared to daytime. The largest daily fluxes and most pronounced diurnal variability coincide with seasons when the flux footprint includes the highest proportion of vegetation, suggesting an important role for daytime sequestration and nighttime respiration to control the diurnal and seasonal variation. Carbon dioxide fluxes change little across the year given the absence of a heating season with an annual total mass flux of 6368 Mg CO2 km −2 year −1 . Singapore provides a unique climatic context, and the present long‐term study is expected to add robust statistics from the understudied (sub)tropical region to the global data set of urban energy and carbon dioxide fluxes, which is dominated by work conducted in mid‐ and high latitudes.